Efforts To Increase Achievement Of Ips Learning Through The Method Of Giving Tasks As Learning Independence In Students Class Vi Sdn 14 Lubuk Aur - Mardarizon Mardarizon (Fakultas Sastra Universitas Ekasakti, 2017)
School education has an important role in improving the quality of human resources. School education is a process that involves educators, teaching materials, and learners.